The Impacts of Food Waste Information on Consumer Preferences for Blemished Produce and Implications for Food Retailers. (29th August 2022) - Collart, Alba J.; Interis, Matthew G.; Henson, Chloe'; Maples, Josh
Abstract: Produce that does not meet sellers' esthetic standards may be redirected to alternative uses or wasted, but consumer trends indicate potential marketability of blemished produce. We conduct a nonhypothetical experimental auction to elicit consumer willingness-to-pay (WTP) for produce of varying degrees of blemish and test whether valuations are affected by (1) information on food waste resulting from grocery stores' esthetic standards and (2) additional information on the environmental impacts of food waste. WTP for blemished produce increases as consumers become informed, but the information effects vary by blemishing degree. Market simulations indicate that introducing blemished produce can increase retailer revenue.